Pengembangan Multimedia Interaktif Berbasis Gamifikasi untuk Mata Pelajaran Pendidikan Agama Buddha - Dwika, Evi Sefriani; Utomo, Budi; Mujiyanto, Mujiyanto (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This research aims to develop gamification-based interactive multimedia for Buddhist Religious Education subject for ninth-grade junior high school students. The research method employed Research and Development (R&D) with the ADDIE model through the stages of analysis, design, development, implementation, and evaluation. Research results showed that the developed interactive multimedia has excellent quality (average score of 4.2 or 84%) based on validation by material and media experts. Product implementation demonstrated increased student interest, engagement, and learning motivation. This gamification-based interactive multimedia can be utilized as an innovative learning medium for teachers and students in Buddhist Religious Education subject.